(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
A class of boundary value problems (BVPs) of even order neutral partial functional differential equations with continuous distribution delay and nonlinear diffusion term are studied. By applying the integral average and Riccati's method, the high-dimensional oscillatory problems are changed into the one-dimensional ones, and some new sufficient conditions are obtained for oscillation of all solutions of such boundary value problems under first boundary condition. The results generalize and improve some results of the latest literature.